Comparison of Corneal Optical Quality After SMILE, Wavefront-Optimized LASIK and Topography-Guided LASIK for Myopia and Myopic Astigmatism - Zhang, Yu; Sun, Xiaoxiao; Chen, Yueguo (Frontiers in Medicine, 2022)
Purpose: To compare visual outcomes and corneal optical quality after small incision lenticule extraction (SMILE),wavefront-optimized (WFO) FS-LASIK and topography-guided customized ablation treatment (TCAT) FS-LASIK for myopia. Methods: This prospective case-series study included 283 eyes of 283 myopic patients who underwent SMILE or FS-LASIK. There were 102 eyes, 100 eyes and 81eyes in the SMILE group, WFO group and TCAT group, respectively. The tomography system (Sirius) was used to measure corneal aberrations and optical quality. Results: At postoperative 1 and 6 months, there were no significant differences in uncorrected distance visual acuity and corrected distance visual acuity among the three groups (P > .05). Postoperative manifest refractive spherical equivalent was similar among the groups (P > .05). There was statistically significant difference in cylinder at 1 month among the three groups, with the highest mean value in TCAT group (P < .05). The corneal optical path difference, root mean square of corneal astigmatism and strehl ratio were the most superior in the TCAT group at postoperative 1 and 6 months (P < .05). Conclusion: SMILE, WFO FS-LASIK and TCAT FS-LASIK provided similar visual results. The corneal visual quality after TCAT FS-LASIK was the best.